Measuring corporate bond market dislocations - Nina Boyarchenko; Richard K. Crump; Anna Kovner; Or Shachar (Federal Reserve Bank of New York, 2021)
We measure dislocations in the market for corporate bonds in real time with the Corporate Bond Market Distress Index (CMDI), allowing for the aggregation of a broad set of measures of market functioning from primary and secondary bond markets into a single measure. The index quantifies dislocations from a preponderance-of-metrics perspective, ensuring that the measure of market distress is not driven by any one statistic. We document that the index correctly identifies periods of dislocations, is robust to alternative choices of the aggregation procedure, and provides differential predictive information for future real outcomes relative to common spread measures.
Keywords: G12; G19; C43; E37; 330; corporate bond market conditions; corporate bond spreads; corporate bond issuance; corporate bond liquidity